2021
DOI: 10.1029/2020jd032997
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Surface Processes on a Record‐Breaking Rainfall Event on May 06–07, 2017, in Guangzhou, China

Abstract: A record‐breaking extreme rainfall event with a maximum rainfall amount over 24 h of 524.1 mm occurred in Guangzhou, China, on May 06–07, 2017. To study the impact of land surface processes on this extreme rainfall, two 21‐member convective‐permitting ensemble forecasts over South China were performed based on two land surface models (LSMs), Noah and Community Land Model (CLM), and 21 forecasting members of the Global Ensemble Forecast System (GEFS). The results showed that, in general, members using the Noah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 103 publications
(96 reference statements)
0
29
0
Order By: Relevance
“…The impact of uncertainties in the initial condition during prediction might be dominant, especially at short ranges. Therefore, we chose 11 members (gec00-gep10) of the NCEP Global Ensemble Forecast System (GEFS) [42] as the initial condition and boundary condition of WRF to discuss the atmospheric mitigating effects with different WRF-related methods in DInSAR.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The impact of uncertainties in the initial condition during prediction might be dominant, especially at short ranges. Therefore, we chose 11 members (gec00-gep10) of the NCEP Global Ensemble Forecast System (GEFS) [42] as the initial condition and boundary condition of WRF to discuss the atmospheric mitigating effects with different WRF-related methods in DInSAR.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Studies found that some hot weather is sensitive to near-surface conditions and LSCs [4,8,9]. Therefore, the impact of LSC is becoming increasingly important for understanding hot weather in EC [10].…”
Section: Introductionmentioning
confidence: 99%
“…The land surface has long been recognized as second in importance only to oceansurface temperature as a driver of climate [11,12]. LSCs, which are a crucial part of the land-surface model and the basic forcing parameters of land-surface boundary conditions [13], can affect the distribution of land-surface energy fluxes and local or regional mesoscale circulation [10,14]. A better description of land-surface characteristic parameters (LSCPs) can improve regional land simulation, and even improve land-atmosphere interactions [13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, climate models have reasonable con dence in the simulation of global surface air temperature (SAT), climate extremes, atmospheric circulation and other elements (Zhou et al, 2006;Lorenz R et al, 2014;Sillmann J et al 2013aSillmann J et al , 2013bZhou et al 2014;Chen and Sun, 2015;Gao et al, 2021), however, there is a large uncertainty in the models' simulations of DTR. The IPCC Fifth Assessment Report (2013) indicated that the CMIP5 model can well reproduce the large-scale surface temperature patterns, but that in many regions there are large uncertainties in the trends and possible interpretations of DTR (Christy J R, et al, 2006;Fall et al, 2011;Zhou and Ren, 2011).…”
Section: Introductionmentioning
confidence: 99%